Antibiotics in Agroecosystems: Introduction to the Special Section. Issue 2 (1st March 2016) - Franklin, Alison M.; Aga, Diana S.; Cytryn, Eddie; Durso, Lisa M.; McLain, Jean E.; Pruden, Amy; Roberts, Marilyn C.; Rothrock, Michael J.; Snow, Daniel D.; Watson, John E.; Dungan, Robert S.
Abstract : The presence of antibiotic drug residues, antibiotic resistant bacteria, and antibiotic resistance genes in agroecosystems has become a significant area of research in recent years and is a growing public health concern. While antibiotics are used in both human medicine and agricultural practices, the majority of their use occurs in animal production where historically they have been used for growth promotion, in addition to the prevention and treatment of disease. The widespread use of antibiotics and the application of animal wastes to agricultural lands play major roles in the introduction of antibiotic‐related contamination into the environment. Overt toxicity in organisms directly exposed to antibiotics in agroecosystems is typically not a major concern because environmental concentrations are generally lower than therapeutic doses. However, the impacts of introducing antibiotic contaminants into the environment are unknown, and concerns have been raised about the health of humans, animals, and ecosystems. Despite increased research focused on the occurrence and fate of antibiotics and antibiotic resistance over the past decade, standard methods and practices for analyzing environmental samples are limited and future research needs are becoming evident. To highlight and address these issues in detail, this special collection of papers was developed with a framework of five core review papers that address the (i) overall state of science of antibiotics and antibiotic resistance in agroecosystems using a causal model, (ii) chemical analysis of antibiotics found in the environment, (iii) need for background and baseline data for studies of antibiotic resistance in agroecosystems with a decision‐making tool to assist in designing research studies, as well as (iv) culture‐ and (v) molecular‐based methods for analyzing antibiotic resistance in the environment. With a focus on the core review papers, this introduction summarizes the current state of science for analyzing antibiotics and antibiotic resistance in agroecosystems, discusses current knowledge gaps, and develops future research priorities. This introduction also contains a glossary of terms used in the core reivew papers of this special section. The purpose of the glossary is to provide a common terminology that clearly characterizes the concepts shared throughout the narratives of each review paper. Core Ideas: Antibiotic resistant bacteria are an emerging threat to human, animal, and ecological health. Agroecosystems often contain elevated levels of antibiotics and antibiotic resistance. The impact of antibiotics at low concentrations in the environment is not fully known. Research is needed to understand the spread of antibiotic resistance within and beyond agroecosystems. Standardized approaches will help bring a consensus among scientific community datasets.